(untitled) (Sudurpaschim Spectrum, 2024)
Nepali modernity had encountered challenges in its development in the 1960s because King Mahendra Shah (1920-1972) had risen to power, thereby derailing the course of for modernity. He believed that democratic institutions and liberal values hindered the essential course of Nepali society and its traditional virtues. In the name of inventing a political system that suited the clime and soil of the nation, he dissolved the parliament, overthrew popularly elected Prime Minister B. P. Koirala (1914-1982), and implemented "partyless democracy" (?) in the name of the Panchayat system. This study has examined the tension, resulting from the tussle between the conservative camp and the liberal values in Nepal’s quest for modernity in the 1960s. Mahendra Shah outlawed democracy to initiate the material transformation and industrialization in Nepal. Koirala and his associates were a group of visionaries who held liberal values. King Shah’s project of modernity entailed self-postponement as it focused on achieving material transformation without transforming the consciousness of people and without allowing people’s participation in the making of a nation by treating the visionary leaders as exiles from the political system. Methodologically, the paper applies new historicist reading of the texts to explore and analyze quest of modernity in Nepal in the 1960s. By analyzing Shah’s speeches, and Koirala’s speech and autobiographical writings, the paper rereads Nepal’s quest for modernity in the 1960s.